Turkic Communities in South Trans-Urals in the 15th–17th centuries: National, Administrative, Territorial, Ethnosocial Transformations. - D.N. Maslyuzhenko; G.Kh. Samigulov (Золотоордынское обозрение)
Research objectives: The article reads on the settlement on and the economic use of the south Trans-Urals territories by Turkic communities. Research materials: Published and unpublished sources: books of official orders in the Russian state, chronicles, acts, diplomatic documents, archaeological data, etc. Results and novelty of the research: Traditionally, administrative divisions of Ural and Trans-Urals are considered to be a sort of a naturally emerged structure. Having analyzed the sources, we may conclude: the system of counties’ (uyezd) division, as introduced by the Russian state, did not consider the allocation of the communities and their economic management mode. Cattle breeding practices of the local Turks determined the specifity of their economic activities. Many Turks’ volosts (ancestral territories) were compound and consisted of two parts: the winter part and the summer one. These two parts could be quite long-distance, divided by the Urals and upon being included into the Russian state they were designated to different uyezds. For instance, one part of Tersyak volost was assigned to Verkhoturskiy uyezd and the second – to Tyumensky uyezd; the western part of the Myakotinskaya (Bakatin) volost was located in Ufimsky uyezd and the eastern – in Tyumensky uyezd, which was in the lower reach of the Iset and Pyshma rivers. Consequently, by the moment of being merged into the Russian state, the territories indicated below were economically managed by the local Turks: South Trans-Urals and a part of Cis-Urals, including the territories in the upperstreams of the Ufa and Chusovaya rivers, along the Pyshma and Iset rivers, partially the Tura river, and Tobol between the outflows of the Miass and Tura. The given practice arose in the late Middle Ages and was intimately connected with Shibanids’ claims who ruled in Tyumen and Siberian Khanates. They claimed not only to the territories in the south of West Siberia, Aral Sea region and Syrdarya region, but also to the Cisuralian area. This was reflected as in their ambition to take the Kazan throne or to collect yasak from the Cisuralian area including Bulgar, so in introduction of their direct rule on the Bashkir Cis-Urals. The political space unity and nomadism similar to common local Turkic groups’ living could become a significant factor for that, as well as the territories united by trading routes. The same factors facilitated the migration of sizable groups from Trans-Urals and the south of West Siberia to Cis-Urals, as it happened to Tabyn tribe.